The Comparison of Cooperative Learning JIGSAW type with Props and Conventional Learning on Students Learning Outcomes - Analisa Purwanti (Universitas Islam Jember, 2016)
The purpose of the research to know the differences in student learning outcomes between the taught by using cooperative learning model with JIGSAW type through the use of props with conventional learning and to know which learning outcomes are better between those taught by using cooperative learning model with JIGSAW type through the use of props with conventional learning. The kind of the research is comparative with quantitative approach. The subjects of the research are students of class VIII MTs Negeri 1 Jember. With the data collecting method that used are test and documentation. The data analysis method that used are quantitative using Man Whitney and test z test. The result of the research there are differences of students' learning outcomes that taught by using cooperative learning model with JIGSAW type through the use of props and conventional learning, and better learning outcomes are taught by cooperative learning model with JIGSAW type.Keywords: JIGSAW, conventional, and mathematical learning outcomes